Dreams of Tomorrow - Alade, R.B (Evans Brothers [Nigeria Publishers] Limited, 1990)
Dreams of Tomorrow is a fiction based on the influence of childhood experiences on growth, development and future,life of a Nigerian Child. It is capable of helping a young person build worthwhile ambition and to follow this up with determination into achievement.
Keywords: Fiction; Juvenile Literature